Weed Management in Soybeans - Jay A. Ferrell; Greg E. McDonald; Pratap Devkota (EDIS, 2021)
Successful weed control is one of the most important practices for economical soybean production in Florida. This 10-page publication discusses weed control methods for soybean growers. Written by J. A. Ferrell, G. E. MacDonald, and P. Devkota, and published by the UF/IFAS Agronomy Department, revised January 2021.